Efeitos da dermotonia no processo de cicatrização da ferida após colecistectomia laparotômica - Machado, Andrea Vasconcelos (2011)
The surgical wound is a factor of great interest for health field professionals, due to the complexity of cicatricial process. Dermotony is a noninvasive painless technique applied in a continual or pulsed way in order to decongest tissues by stimulating dermalgical zones. However, there are few scientific works which relate to its technical use. This study has aimed at evaluate edema in abdominal area; verify cicatricial retraction; evaluate dermotony in post-operative pain; verify inflammatory process. It is an experimental study of a clinical randomized trial character, in which 20 female patients have been submitted to laparotomy cholecistectomy surgery in the University Hospital of the Federal University of Sergipe, from June to November, 2010. Patients have been randomly separated in group A (treatment) and group B (control). Edema, cicatricial retraction, pain and inflammatory process have been the researched variables. In between-group comparison, for all variables, the treatment has not differentiated them eventually. Although, within-group comparison has showed a reduction from 0,77 to 1,36% in cirtometry, 5,22% in perimetry, and concerning pain perception, its reduction has reached 82,98%, being more evident within 4th and 5th administration. Nevertheless, it has not been verified within-group differences in prostaglandin measurement. At the end of the study, it has been concluded that in between-group comparison, dermotony has not differentiated them, though in within-group correlation, the results have been satisfactory for all variables, except for prostaglandin dosage.